Model Realistic Mathematic Education (RME) Berbasis Etnomatematika Memperkuat Fondasi Pemahaman Konsep Matematika - Nurjanah, Erni; Al Hadiq , M. Furqon; Rusliana , Elzan Tanzania (Didactical Mathematics, 2025)
The problem raised in this research is the lack of understanding of mathematical concepts by Cilangla Elementary School students. The aim of this research is to see the impact of implementing the ethnomathematics-based Realistic Mathematic Education (RME) model on understanding concepts in elementary school students' mathematics learning. This research uses a quantitative experimental design, the quantitative type used is Quasi Experimental Design. The following quasi-experimental design is used using the Nonequivalent Control Group Design type. The samples taken and used in this research were 30 students at SDN Cilangla class 3 B used as the experimental group, and SDN Cilangla class 3 A totaling 30 students used as the control group. The research instrument used was an essay test. The data taken will later be processed and measured using measurement instruments used to analyze data in this research using statistical tests, namely the independent sample t-test. Based on the results of the t test, it shows that it has a value of t = 2,400 and sig = 0.020 < 0.05, the result of regression test show thitung 2,136> ttabel 2,056 which means that there is a significant influence between the ethnomathematics-based realistic mathematics education or (RME) learning model on students' understanding of mathematical concepts. Apart from that, based on the latest data the average value of the experimental class was 85.07 and the control class 73.37. This shows that the use of the Ralistic Mathematical Education (RME) learning model based on ethnomathematics has an influence on students' understanding of mathematical concepts at SDN Cilangla for the 2022/2023 academic year.